Wood Microstructure And Identification Key of Selected Species Of Poplar (Populus sp.) - YADAV, RONAK; GUPTA, SANGEETA (Indian Forester, 2023)
The study is based on the examination of eleven wood samples from four species of genus Populus viz. Populus alba L., Popuius ciiiata Wall, ex Royle, Popuius euphratica Oliv. and Populus nigra L. Internationally acclaimed standard laboratory procedure was followed to make permanent slides. The qualitative and quantitative characteristics were recorded as per the feature list given by International Association of Wood Anatomists (lAWA) for hardwood identification. Photomicrographs were taiten from three sections i.e. Transverse section, Tangential and Radial longitudinal sections to study the wood microstructure and recorded the diagnostic features in each taxon. The selected Populus species show both similar and dissimilar qualitative wood anatomical characteristics within and among studied species. The identification key developed from the studied microstructures was used to distinguish the studied species.